Karakteristik Gugus Fungsi dan Kekuatan Impak Material Komposit Berpenguat Serat Serbuk Daun Nanas - Tanjung, Iqbal; Lubis, Riadini Wanty; Nofri, Irfan; ., Affandi; Siregar, Chandra A; Siregar, Ahmad Marabdi; Efrida, Rizki (Rekayasa Material, Manufaktur dan Energi, 2025)
The objective of this study is to investigate the impact strength and functional group characteristics, as identified through FTIR spectroscopy, of composite materials reinforced with pineapple leaf powder fibers that have undergone physical property enhancement via alkali treatment (NaOH). A series of processes were conducted to produce the pineapple leaf powder, starting with drying fresh pineapple leaves until they turned brown. The dried leaves were then cleaned and soaked in a 5% NaOH solution for durations of 1, 3, 5, 7, and 9 hours to modify their physical properties. After treatment, the leaves were rinsed thoroughly and oven-dried at 60°C for 5 hours. The dried leaves were subsequently ground and sieved using a 150-mesh screen. This study involved two main observations: functional group analysis using FTIR spectroscopy and mechanical performance evaluation through impact testing. A total of 30 composite specimens were prepared and fabricated using a stepwise lamination method, following the ASTM D256 impact testing standard. The results indicate that alkali treatment progressively degraded the hemicellulose and lignin content in the pineapple leaf fibers, significantly enhancing the impact energy absorption of the composite material. However, extended treatment durations adversely affected the fiber quality, leading to structural damage and reduced interfacial cohesion between the composite components.